A switchable terahertz metamaterial absorber between ultra-broadband and dual bands - Ren, Zhi; Wang, Wanqing; Zhao, Yinghui; Chang, Siqi; Ren, Guanhua; Li, Songtao; Wang, Ruoxing (Frontiers in Physics, 2023)
Based on the phase change properties of vanadium dioxide (VO2), we propose a terahertz metamaterial absorber that can be switched flexibly between ultra-broadband and dual bands. The absorber consists of a resonator array above a conductive ground layer separated with a dielectric spacer, which includes four square-loop VO2 resonators and a crossed gold resonator in each unit cell. By changing the conductivity of VO2 through thermal control, the absorber can achieve the switching between ultra-broadband absorption and dual-band absorption. Simulation results show that at high temperature, the absorber realizes more than 90% absorption bandwidth in the range of 3.98 THz to 9.06 THz, which can be elucidated by the wave-interference theory and impedance matching theory. At low temperature, up to 95% of the dual-band absorption occurs at 5.95 THz and 6.95 THz, which originates the dipole mode and nonlocal surface-Bloch mode of metal resonators. In addition, the absorber has the advantages of polarization-independence and wide-angle absorption. Compared with previous studies, our design can switch between two absorption modes and its absorption performance is greatly improved. The proposed absorber design scheme is expected to expand terahertz devices and enable a variety of applications in the terahertz range, such as modulation, sensing, stealth, and switching devices.